110 UK multiple sclerosis service audit of 70 centres: MS-MDTs. Issue 6 (27th May 2022) - Rog, David; Hobart, Jeremy; Mathews, Joela; ,
Abstract : Introduction: The UK MS service audit builds upon GIRFT's recommendation for disease-specific data. Here, we address MS-specific Multidisciplinary Team (MS-MDT) meetings, an NHSE requirement for services prescribing disease modifying treatments (DMTs), although the wider MS-MDT parameters are less clear. Aim: To document the characteristics and variability in UK MS-MDTs. Methods: We asked all MS services to complete service questionnaires, supplemented with individual clinician interviews. Specifically, we asked about occurrence, frequency, who attends, and numbers and types of patients discussed at, MS-MDTs. Results: Forty-six of the 70 centres (68%) had an MS-MDT, 63% were weekly. Neuroradiologists attended only 49%, MS Coordinators 79% and Neuropharmacists 50%, of meetings. Neurology SpRs (73%) and Research Registrars (62%), attended the majority of MS-MDTs. A mean of 9 patients (range 1–40, SD 7) were discussed, predominantly complex patients and/or those considered for high efficacy DMTs. Conclusions: There was considerable variation in the occurrence, frequency, composition and types of patients discussed at UK MS MDTs. Neuroradiologists absence is concerning, given the central role of MRI in MS clinical decision-making. Neuropharmacists and MS coordinators absence, limits the wider benefits from MS Team members. The MS-MDT is a regular touch point and a significant educational opportunity for the whole team, including trainees. We recommend that the UK MS community defines the param- eters of an MS-MDT so that these can be consistently implemented, through job-planning, across services. david: rog@srft.nhs.uk 80